The controversy of klotho as a potential biomarker in chronic kidney disease - Li-Xia Yu; Sha-Sha Li; Min-Yue Sha; Jia-Wei Kong; Jian-Ming Ye; Qi-Feng Liu (Frontiers Media S.A., 2022)
Klotho is an identified longevity gene with beneficial pleiotropic effects on the kidney. Evidence shows that a decline in serum Klotho level occurs in early chronic kidney disease (CKD) and continues as CKD progresses. Klotho deficiency is associated with poor clinical outcomes and CKD mineral bone disorders (CKD-MBD). Klotho has been postulated as a candidate biomarker in the evaluation of CKD. However, the evidence for the clinical significance of the relationship between Klotho and kidney function, CKD stage, adverse kidney and/or non-kidney outcomes, and CKD-MBD remains inconsistent and in some areas, contradictory. Therefore, there is uncertainty as to whether Klotho is a potential biomarker in CKD; a general consensus regarding the clinical significance of Klotho in CKD has not been reached, and there is limited evidence synthesis in this area. To address this, we have systematically assessed the areas of controversy, focusing on the inconsistencies in the evidence base. We used a PICOM strategy to search for relevant studies and the Newcastle-Ottawa Scale scoring to evaluate included publications. We reviewed the inconsistent clinical findings based on the relationship of Klotho with CKD stage, kidney and/or non-kidney adverse outcomes, and CKD-MBD in human studies. Subsequently, we assessed the underlying sources of the controversies and highlighted future directions to resolve these inconsistencies and clarify whether Klotho has a role as a biomarker in clinical practice in CKD.